Intestinal parasite infections and associated risk factors in communities exposed to wastewater in urban and peri-urban transition zones in Hanoi, Vietnam. Issue 1 (December 2016) - Fuhrimann, Samuel; Winkler, Mirko; Pham-Duc, Phuc; Do-Trung, Dung; Schindler, Christian; Utzinger, Jürg; Cissé, Guéladio
Abstract Background Infections with intestinal parasites (helminths and intestinal protozoa) are endemic in Southeast Asia and inappropriate management and reuse of wastewater might exacerbate the risk of human infections. In rapidly growing urban settings, little is known about the extent of intestinal parasite infections. We assessed the point-prevalence and risk factors of intestinal parasite infections in population groups differently exposed to wastewater in urban and peri-urban transition zones in Hanoi, the capital of Vietnam. Methods A cross-sectional survey was carried out between April and June 2014 in people aged ≥ 18 years at risk of wastewater exposure from To Lich River: workers maintaining wastewater treatment facilities; urban farmers reusing wastewater; and urban dwellers at risk of flooding events. For comparison, two peri-urban population groups living in close proximity to the Red River were chosen: farmers using river water for irrigation purposes; and people living in the same communities. A single stool sample was subjected to Kato-Katz and formalin-ether concentration methods for the diagnosis of helminth and intestinal protozoa infections. A questionnaire was administered to determine risk factors and self-reported signs and symptoms. Results A total of 681 individuals had complete data records. Highest point-prevalence rates of intestinal parasite infections were observed for peri-urban farmers (30 %). Hookworm andTrichuris trichiura were the predominant helminth species (25 % and 5 %, respectively). Peri-urban farmers were at higher odds of infection with intestinal parasites than any other groups (adjusted odds ratio 5.8, 95 % confidence interval 2.5 to 13.7). Lack of access to improved sanitation and not receiving deworming within the past 12 months were associated with higher infection risk, while higher educational attainment and socioeconomic status were negatively associated with intestinal parasite infections. Conclusions Our results suggest that exposure to wastewater was not directly associated with infection with helminths and intestinal protozoa in different population groups in Hanoi. These findings might be explained by a high level of awareness of health risks and access to safe sanitary infrastructure in urban areas. The high prevalence rates observed in peri-urban farmers call for specific interventions targeting this population group.